SPATIAL ARRANGEMENT AND FURNISHING OF THE CLASSROOM IN THE LATE 18th – EARLY 20th CENTURY - Косенко, Д. Ю. (Art and Design, 2019)
Purpose of the article is to discover features of the arrangement and furnishing of the school learning space in the period of the late 18th – early 20th century. Methodology is based on the historical and cultural method. Source base includes works of art, scientific and technical literature of the period discussed, historical artefacts. In the middle of the 18th century. with the establishment in Europe the state systems of mandatory school education, the forms and methods of study work are changed, and accordingly change the approaches to the spatial organization of the classroom. The fixed front row organization of the learning space emerges, gradually spreads and dominates throughout the reviewed period. Only at the turn of 20th century criticism to this approach appears in progressive education movement, and the search for alternative approaches starts. Thus, late 18th – early 20th century can be considered as a particular period in the development of the educational space organization. This period can be divided in two stages. The initial stage is distinguished by a utilitarian approach to the classroom arrangement, furniture assembly and the shaping of furniture. New stage of development of the school educational space begins approximately in the 1840s in the USA and in the 1860s in Europe, characterized by a scientific and hygienic approach. At this stage, the industrial production of school furniture also arises, aesthetic factors begin to play a certain role in furniture shaping. Scientific novelty. The development of the spatial organization of school classroom of the late 18th – early 20th treated as a particular period of development of the learning space. The time frames for the reviewed period are specified basing on the characteristic features of classroom furniture and the arrangement of classroom. The stages of development of classroom furniture within the studied period are identified and characterized.